Impactos socioeconômicos e ambientais do avanço da fronteira pecuária em São Félix do Xingu no estado do Pará, no período de 1985 a 2022: apresentação de mini atlas territorial - SANTOS, Amanda Karolina Santos dos (Universidade Federal do Pará, 2025)
The municipality of São Félix do Xingu, located in the southeastern mesoregion of the state of Pará, is the second largest municipality in Pará and the sixth largest in Brazil in terms of territorial extension, with 84,212.903 km2. It has the largest municipal cattle herd, reaching 2.5 million head in 2022. In that same year, the municipality totaled 24.31% of its area deforested, due to the constant process of converting forests into pasture areas. In this sense, this dissertation work deals with the advance of the livestock frontier in São Félix do Xingu and its effects on changes in land use and cover, and its environmental and socioeconomic impacts. The general objective of this research was to investigate the role of the advance of the livestock frontier in the dynamics of deforestation in São Félix do Xingu, for the period from 1985 to 2022. The methodology was guided by the typologies of qualitative, quantitative and exploratory research. Annual land use and land cover maps and data from MapBiomas in GeoTiff format for the period between 1985 and 2022, deforestation data from the Satellite Monitoring Project for Deforestation in the Legal Amazon (PRODES) and data from the Municipal Livestock Farming Program (PPM/IBGE) were used. The results showed continued growth in deforestation during the period studied, confirming that the livestock frontier continues to advance over the natural resources of this municipality beyond the non-designated public forests, also advancing over areas protected by law, which demonstrated that the frontier remains open and controlled by the institutions present in this municipality.